Efficient Power Coupling in Directly Connected Photovoltaic‐Battery Module. Issue 3 (14th December 2022) - Shcherbachenko, Sergey; Astakhov, Oleksandr; Chime, Ugochi; Kin, Li-Chung; Ding, Kaining; Pieters, Bart; Rau, Uwe; Figgemeier, Egbert; Merdzhanova, Tsvetelina
Abstract : Due to the intermittent nature of solar irradiance and the temporal mismatch between solar power generation and consumption profiles, the combination of photovoltaic (PV) devices with energy storage is essential. The maximum power point tracking (MPPT) devices are commonly used for the connection of PV to electrochemical storage and load, ensuring power matching and providing flexibility in system design. Herein, the usability of direct PV‐battery coupling as an alternative to MPPT under realistically varied battery state of charge (SoC), irradiance, temperature of the PV module, and applied load is investigated. A stable power coupling factor above 90% is demonstrated between a silicon heterojunction solar module and Li‐ion battery in the whole range of measured SoC (12.5–75%) and a wide range of load power. The dependence of power coupling on temperature and irradiance is calculated and compared to the power generation profile of a PV plant installed in southern Germany. In the region of highest power generation, the direct connection provides coupling efficiencies above 95%, reaching 100%, for the usable range of battery SoC. These results show that direct PV‐to‐battery coupling is feasible for a variety of practical applications and scales. Abstract : The coupling efficiency of directly connected solar cell and battery in a wide range of module temperature, irradiance, battery state of charge, and applied load is explored. These results show a coupling efficiency of 95% or above in a wide range of conditions and that direct connection can be a feasible alternative to power converters for practical application.